Multidrug-Resistant Shigellosis among Children Aged below Five Years with Diarrhea at Banadir Hospital in Mogadishu, Somalia - Bilan Sheikh Ali Nor; Nelson Chengo Menza; Abednego Moki Musyoki (Canadian Journal of Infectious Diseases and Medical Microbiology)
Globally, shigellosis remains the second leading cause of diarrhea-associated deaths among children under five years of age, and the infections are disproportionately higher in resource-limited settings due to overcrowding, poor sanitation, and inadequate safe drinking water. The emergence and global spread of multidrug-resistant (MDR) Shigella are exacerbating the shigellosis burden. We adopted a cross-sectional study design to determine the distribution and antimicrobial susceptibility (AST) patterns of Shigella serogroups among children aged below five years presenting with diarrhea at Banadir Hospital in Mogadishu, Somalia, from August to October 2019. Stool and rectal swab samples were collected from 180 children consecutively enrolled using a convenient sampling technique and processed following standard bacteriological methods. AST was determined using the Kirby–Bauer disc diffusion method and interpreted as per the Clinical Laboratory Standard Institute (2018) guidelines. Shigellosis prevalence was 20.6% (37/180), and S. flexneri (26/37 (70.3%)) was the predominant serogroup. All the serogroups were 100% resistant to ampicillin (AMP), trimethoprim-sulfamethoxazole (SXT), and tetracycline (TE). Ceftriaxone (CRO) resistance was the highest among S. sonnei (66.7%) isolates. 19.2% of S. flexneri and S. sonnei (50%) serogroups were resistant to ciprofloxacin (CIP), but all S. dysenteriae type 1 isolates remained (100%) susceptible. Forty percent of CIP-susceptible S. dysenteriae type 1 were resistant to CRO. Seven MDR Shigella phenotypes were identified, dominated by those involving resistance to AMP, SXT, and TE (100%). Our findings showed a high prevalence of shigellosis with S. flexneri as the most predominant serogroup among children under five years of age in Banadir Hospital, Somalia. AMP and SXT are no longer appropriate treatments for shigellosis in children under five years in Banadir Hospital. MDR Shigella strains, including those resistant to CIP and CRO, have emerged in Somalia, posing a public health challenge. Therefore, there is an urgent need for AMR surveillance and continuous monitoring to mitigate the further spread of the MDR Shigella strains in Banadir Hospital and beyond.